The Mediating Role of Trust in Digital Payment Adoption: The Influence of Perceived Ease of Use on Usage Decision - Damaris Y. Koli; Jemmy J. S. Dethan; Alfred G. O. Kase (Indonesian Journal of Enterprise Architecture, 2026)
The rapid expansion of digital payment technologies has transformed financial transaction behavior, particularly in emerging urban environments. However, adoption decisions are influenced not only by technological functionality but also by psychological factors. This study examines the effect of perceived ease of use on digital payment usage decisions, with trust positioned as a mediating variable. A quantitative approach was employed using survey data collected from 96 digital payment users in Kupang City, Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived ease of use has a significant positive effect on trust (β = 0.870, p < 0.001) and usage decision (β = 0.612, p < 0.001). Trust also significantly influences usage decision (β = 0.295, p = 0.020) and partially mediates the relationship between perceived ease of use and usage decision. The model demonstrates substantial explanatory power, with R² values of 0.757 for trust and 0.776 for usage decision, and a good model fit (SRMR = 0.042). These findings extend the Technology Acceptance Model by demonstrating that usability influences digital payment adoption through both direct functional pathways and indirect trust-building mechanisms. The study highlights the strategic importance of integrating usability and trust to promote digital payment adoption in emerging urban contexts.